1998
DOI: 10.1103/physreva.58.4484
|View full text |Cite
|
Sign up to set email alerts
|

Angular distributions and rotational excitations for electron scattering from ozone molecules

Abstract: Ab initio quantum scattering calculations are carried out for the O 3 molecule, in its ground electronic state, from which low-energy electrons are scattered in the gas phase. The results of the computations are compared with the existing experimental angular distributions for elastic ͑rotationally summed͒ scattering processes and for rotationally inelastic cross sections. The agreement of the present calculations with the available experiments is found to be remarkably good and the corresponding efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…The scattering orbitals are distributed by symmetry as follows: 35 for A 1 , 15 for B 1 , 27 for B 2 , and 10 for A 2 . Our calculated dipole moment is 0.76 Debye and the results of [3,4,[6][7][8] are 0.86, 0.84, 0.91 and 0.76 Debye respectively. The experimental dipole moment is 0.53 Debye [16].…”
Section: Computational Proceduresmentioning
confidence: 47%
See 2 more Smart Citations
“…The scattering orbitals are distributed by symmetry as follows: 35 for A 1 , 15 for B 1 , 27 for B 2 , and 10 for A 2 . Our calculated dipole moment is 0.76 Debye and the results of [3,4,[6][7][8] are 0.86, 0.84, 0.91 and 0.76 Debye respectively. The experimental dipole moment is 0.53 Debye [16].…”
Section: Computational Proceduresmentioning
confidence: 47%
“…Integral cross section for O 3 . Full curve, our pseudopotentials results; broken curve, theoretical static-exchange results of [6]; chain curve with triangles, theoretical results of [3]; dotted curve, theoretical results of [7]; chain curve with circles, theoretical results of [8]; diamonds, experimental data of [2].…”
Section: Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as shown by Faure & Tennyson (2001) in the case of linear molecular ions, the key parameter in the rotational excitation process is the dipole moment value which dictates the magnitude of dipole allowed transitions and, consequently, the relative importance of dipole forbidden transitions. For example, in the case of ozone which has a small dipole moment (0.53 D), Gianturco, Paioletti & Sanna (1998b) found that transitions with Δ J = 2 have cross‐sections slightly larger than those with Δ J = 1. This merely reflects the fact that the importance of dipole forbidden transitions is inversely proportional to the dipole moment value of the target (neutral or charged).…”
Section: Resultsmentioning
confidence: 99%
“…In the two panels both the singlet (1) and triplet (3) components of the calculations are shown for the four IRs contributing to the process. Since the elastic cross sections for polar targets are known to diverge in the forward direction at low scattering energies (see, e.g., Gianturco et al 1998), we did not carry out calculations below 1 eV, where the dipole value is expected to mostly show its effects. Furthermore, as we are interested here in the study of the molecular nature and of the energy locations of the single-particle resonances of the title system, we have not implemented the usual correction to this low-energy divergent behaviour at this stage.…”
Section: The Calculation Of Cross Sectionsmentioning
confidence: 99%